A double-layer hydrogel patch for on-demand drug release in response to pH and a preparation method thereof
By using curcumin-loaded sodium alginate microspheres and tannin acid in a double-layer hydrogel patch, the pH-sensitive polymer characteristics of sodium alginate are used to achieve selective drug release based on wound pH value, solving the problem of improper release of antibacterial drugs in the prior art, and improving the wound healing effect.
Patent Information
- Application Number
- CN202510061145.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The prior art cannot perform selective drug release based on changes in wound pH, resulting in a sudden release of antibacterial drugs, which may affect the wound healing process.
Using a bilayer hydrogel patch that responds to pH-on-demand release, drug release is controlled when wound pH changes by using curcumin-loaded sodium alginate microspheres and tannins in the release layer.
Selective drug release based on wound pH is achieved, which improves the antibacterial and anti-inflammatory effect of wounds and promotes wound healing.
Smart Images

Figure CN119454664B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of medical technology, and in particular relates to a double-layer hydrogel patch that releases drugs on demand in response to pH and a preparation method thereof. Background Art
[0002] The skin is the largest organ system in the human body. Due to its direct contact with the outside world, the skin is susceptible to various stimuli, resulting in trauma, burns, lacerations, etc., so the skin has become one of the most vulnerable tissues. Skin wound healing is a complex process involving the orderly interaction of inflammatory cells, collagen, inflammatory factors and extracellular matrix in time and space, which is divided into four consecutive processes, including hemostasis, inflammation, proliferation and remodeling. However, at any stage of wound healing, various factors may cause abnormal healing, such as infection, excessive inflammation, diabetes and secondary trauma. Once the wound is infected, it will cause local or even systemic inflammatory reactions, which may even threaten the patient's life safety in severe cases. Traditionally, the treatment of infected wounds relies on thorough debridement, reasonable use of antibiotics and appropriate wound care. However, with the increase of drug-resistant strains and the increasing prominence of chronic wound infection, traditional treatment methods are facing challenges.
[0003] With the deepening of research on natural antimicrobial active molecules, more and more researchers have begun to use hydrogels as drug delivery systems to prepare wound dressings, using the safe antibacterial properties of natural antimicrobial compounds to inhibit the proliferation of bacteria in the wound microenvironment and kill bacteria, thereby promoting wound healing. In addition, hydrogels are widely used in wound dressings due to their high water content, high biocompatibility, and absorption of wound exudate. Therefore, loading natural active substances into hydrogel wound dressings to deliver drugs to infected wounds, creating a suitable microenvironment for wound healing by killing colonized bacteria and anti-inflammatory methods, and thus promoting healing has become an effective strategy.
[0004] However, as one of the basic parameters of the wound microenvironment, intracellular and extracellular pH can effectively affect cellular processes (enzyme activity, macromolecular synthesis, metabolite transport) and cell cycle processes (inflammation, collagen formation and angiogenesis) in four stages. Intact skin is naturally acidic, with a pH of 4-6. Once a wound is formed by external stimulation, the pH value on the wound surface increases due to microvascular leakage, close to the physiological pH that adapts to bacterial infection. Wound colonization with bacteria will further lead to inflammation and prolong the wound healing cycle, and the pH value will become more alkaline, usually between 7.5-8.9. In addition, passive drug delivery by direct encapsulation in hydrogels is the main delivery method for antimicrobial drugs. However, this may lead to the sudden release of antimicrobial substances. Unnecessary delivery of antimicrobial substances may affect the wound healing process through dysbiosis of the skin microbiome and systemic toxicity, which is incompatible with the complex and dynamic healing process of wounds. Therefore, it is a safe and effective strategy to prepare smart hydrogels by utilizing the changes in the pH of the wound microenvironment and selectively release drugs by responding to the pH at the wound. In actual applications, when hydrogel dressings are applied to wounds, they often have problems such as poor water retention and susceptibility to contamination, which greatly limit their clinical efficacy and wide application. Summary of the invention
[0005] The purpose of the present application is to provide a double-layer hydrogel patch that releases drugs on demand in response to pH and a preparation method thereof, aiming to solve the problem that wound dressings in the prior art cannot selectively release drugs based on changes in pH at the wound.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a method for preparing a double-layer hydrogel patch that releases drugs on demand in response to pH, comprising the following steps: preparing sodium alginate microspheres loaded with curcumin using a microfluidic device; preparing a drug-releasing layer hydrogel: dissolving acrylamide and tannic acid in deionized water, adding the prepared sodium alginate microspheres loaded with curcumin and uniformly dispersing them by ultrasound, adding a cross-linking agent and an initiator after the dispersion is completed, and incubating in an oven after complete dissolution to obtain a drug-releasing layer hydrogel; preparing a double-layer hydrogel patch: uniformly mixing a PDMS component of polydimethylsiloxane and a curing agent, casting them on the prepared drug-releasing layer hydrogel, and then putting them in an oven for curing to form a protective layer on the drug-releasing layer to obtain a double-layer hydrogel patch.
[0008] According to a preferred embodiment, the step of preparing sodium alginate microspheres loaded with curcumin using a microfluidic device also includes: preparing an aqueous phase liquid: preparing a sodium alginate / curcumin aqueous solution, a calcium chloride aqueous solution, a sodium hydroxide aqueous solution and an ethylenediaminetetraacetic acid solution respectively; mixing the calcium chloride aqueous solution and the ethylenediaminetetraacetic acid solution in a certain proportion and adjusting the pH to 7.2-7.4 with a sodium hydroxide aqueous solution to obtain a mixed component, and mixing the sodium alginate / curcumin aqueous solution with the obtained mixed component in equal proportions to obtain an aqueous phase liquid; preparing an oil phase liquid: taking liquid paraffin containing 5% Span-80 as the oil phase liquid; preparing a solidifying liquid: taking liquid paraffin containing 1% acetic acid and 5% Span-80 as the solidifying liquid.
[0009] According to a preferred embodiment, the step of preparing sodium alginate microspheres loaded with curcumin using a microfluidic device further includes: using a first syringe to absorb an aqueous phase liquid and then fixing it on a first syringe pump, using a second syringe to absorb an oil phase liquid and then fixing it on a second syringe pump, wherein the outlet end of the first syringe and the outlet end of the second syringe are connected to a capillary glass tube; firstly running the second syringe pump to exhaust the air in the system, and then running the first syringe pump, when small balls with uniform spacing appear in the capillary glass tube, placing a container containing a solidifying liquid under the capillary glass tube so that the end of the capillary glass tube is located below the liquid surface, and sodium alginate microspheres loaded with curcumin will be generated in the container, and after solidification for a certain period of time, the microspheres are washed with isopropanol and deionized water, and freeze-dried for standby use.
[0010] According to a preferred embodiment, the flow rate of the aqueous phase liquid in the first syringe pump is 0.02 mL / min, and the flow rate of the oil phase liquid in the second syringe pump is 0.27 mL / min.
[0011] According to a preferred embodiment, the curing time is 30 minutes.
[0012] According to a preferred embodiment, in the step of preparing the drug-releasing layer hydrogel, the temperature of the oven is 50° C. and the incubation time is 1 hour.
[0013] According to a preferred embodiment, in the step of preparing the drug-releasing layer hydrogel, the cross-linking agent is N,N'-methylenebisacrylamide, and the initiator is ammonium persulfate.
[0014] According to a preferred embodiment, in the step of preparing a double-layer hydrogel patch, the temperature of the oven is 50° C., the curing time is 1 hour, and the mass ratio of the PDMS component of the polydimethylsiloxane to the curing agent is 10:1.
[0015] In a second aspect, the present application further provides a double-layer hydrogel patch that releases drugs on demand in response to pH, which is prepared by the preparation method described in any one of the first aspects.
[0016] According to a preferred embodiment, it comprises a drug-releasing layer and a protective layer, and the protective layer is attached to the surface of the drug-releasing layer.
[0017] Based on the above technical solution, the double-layer hydrogel patch for on-demand drug release in response to pH and the preparation method thereof of the present application have at least the following beneficial technical effects:
[0018] The double-layer hydrogel patch prepared in the present application that responds to pH and releases drugs on demand can release different drugs for antibacterial and anti-inflammatory effects based on the pH value of the wound, so that the wound has a better healing effect.
[0019] In the preparation method of the present application, the natural polyphenolic substance tannic acid is used in the drug release layer hydrogel. The catechol functional group it possesses can give the hydrogel strong adhesion, and it can stably adhere to the wound while also tightly combining the protective layer with the drug release layer. In addition to the adhesion function, tannic acid can also be used as a natural active drug to be quickly released in the early stage of healing of infected wounds, exerting preliminary antibacterial and anti-inflammatory effects. Sodium alginate is a pH-sensitive polymer with a large number of carboxyl groups. Under acidic conditions, most of the carboxyl groups exist in the form of -COOH, which will lead to polymer-polymer bonding, resulting in shrinkage, reduced pore size and reduced drug release; under neutral or weakly alkaline conditions, the carboxyl groups in the polymer are ionized and mainly exist in the form of -COO-, which causes the polymer to swell due to electrostatic repulsion between -COO- groups, thereby causing degradation, increasing pore size and increasing drug release. If the wound becomes inflamed due to bacterial infection and develops into a chronic infected wound, the pH value at the wound will become neutral to alkaline. At this time, the sodium alginate microspheres loaded with curcumin in the drug release layer will degrade and release curcumin. Curcumin will then synergize with tannic acid to achieve antibacterial and anti-inflammatory effects, promoting the healing of chronic infected wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0021] Figure 1 is a tensile performance diagram of the hydrogels prepared with different amounts of tannic acid added in Examples 1 to 4 of the present application, wherein: Figure 1 In the figure, a is a stress-strain curve, and b, c, and d are statistical graphs of the elongation at break, tensile stress, and Young's modulus of the stretching results of different hydrogel samples, respectively.
[0022] Figure 2is a graph showing the adhesion performance of the hydrogels prepared with different amounts of tannic acid added in Examples 1 to 4 of the present application;
[0023] Figure 3 It is a schematic diagram of the microfluidic device in Example 5 of the present application.
[0024] Figure 4 This is a cytotoxicity graph of the drug release layer hydrogel prepared with different Alg@Cur addition amounts in Example 6 of the present application.
[0025] Figure 5 This is a graph of the tensile properties of the drug release layer hydrogel prepared with different Alg@Cur addition amounts in Example 6 of the present application.
[0026] Figure 6 This is a graph of the in vitro degradation performance of the double-layer hydrogel patch prepared in Example 7 of the present application at different pH values.
[0027] Figure 7 This is a diagram of the swelling performance of the double-layer hydrogel patch prepared in Example 7 of the present application.
[0028] Figure 8 is a performance diagram of the Alg@Cur microspheres prepared in Example 5 of the present application, wherein Figure 8 (a) is the morphology diagram of Alg@Cur microspheres, (b) is the particle size statistics diagram of Alg@Cur microspheres, and (c) is the component analysis diagram of Alg@Cur microspheres.
[0029] Fig. 9 This is a test chart of the healing performance of the double-layer hydrogel patch prepared in Example 7 of the present application on infectious wounds.
[0030] In the figure: 1-first syringe pump; 11-first syringe; 2-second syringe pump; 12-second syringe; 13-capillary glass tube; 14-transparent hose. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0032] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0033] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0034] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0036] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as µg, mg, g, kg, etc.
[0037] The present application provides a method for preparing a double-layer hydrogel patch that releases drugs on demand in response to pH, comprising the following steps:
[0038] (1) Preparation of curcumin-loaded alginate microspheres (Alg@Cur) using a microfluidic device;
[0039] Specifically: prepare a sodium alginate / curcumin aqueous solution, a calcium chloride aqueous solution, a sodium hydroxide aqueous solution and an ethylenediaminetetraacetic acid solution respectively; mix the calcium chloride aqueous solution and the ethylenediaminetetraacetic acid solution in a certain proportion and adjust the pH to 7.2-7.4 with a sodium hydroxide aqueous solution to obtain a mixed component; mix the sodium alginate / curcumin aqueous solution and the obtained mixed component in equal proportions to obtain an aqueous phase liquid; the oil phase liquid is liquid paraffin containing 5% span-80; and the solidified liquid is liquid paraffin containing 1% acetic acid and 5% span-80.
[0040] A first syringe was used to absorb the aqueous phase liquid and then fixed on the first syringe pump, and the flow rate was set to 0.02 mL / min. A second syringe was used to absorb the oil phase liquid and then fixed on the second syringe pump, and the flow rate was set to 0.27 mL / min, wherein the outlet end of the first syringe and the outlet end of the second syringe were commonly connected to a capillary glass tube; the second syringe pump was first operated to exhaust the air in the system, and then the first syringe pump was operated. When small balls with uniform spacing appeared in the capillary glass tube, a container containing a solidifying liquid was placed under the capillary glass tube so that the end of the capillary glass tube was located below the liquid surface, and sodium alginate microspheres loaded with curcumin were generated in the container. After curing for 30 minutes, the microspheres were washed with isopropanol and deionized water, and freeze-dried for use.
[0041] (2) Preparation of drug release layer hydrogel: acrylamide and tannic acid were dissolved in deionized water, and the prepared sodium alginate microspheres loaded with curcumin (Alg@Cur) were added and uniformly dispersed by ultrasound. After dispersion, crosslinking agent N,N'-methylenebisacrylamide (MBA) and initiator ammonium persulfate (APS) were added. After complete dissolution, the mixture was placed in an oven at 50°C for incubation for 1 h to obtain a drug release layer hydrogel;
[0042] (3) Preparation of a double-layer hydrogel patch: The PDMS component of polydimethylsiloxane and the curing agent were uniformly mixed in a mass ratio of 10:1, cast on the prepared drug-releasing layer hydrogel, and then placed in a 50°C oven for curing for 1 h to form a protective layer on the drug-releasing layer to obtain a double-layer hydrogel patch.
[0043] The following describes the invention in conjunction with specific embodiments.
[0044] Preparation of drug release layer hydrogel patch.
[0045] Example 1
[0046] Weigh 3 g of acrylamide (AAm) and dissolve it in 10 mL of deionized water to form solution A. Then weigh 6 mg of N, N'-methylenebisacrylamide (MBA) and 30 mg of ammonium persulfate (APS) and fully dissolve them in solution A to form a precursor solution. The precursor solution was incubated in an oven at 50°C for 1 h to obtain PAM hydrogel.
[0047] Example 2
[0048] 4.5 g acrylamide (AAm) and 0.075 tannic acid (TA) were weighed and dissolved in 15 mL deionized water to form solution A. Subsequently, 10 mg N, N'-methylenebisacrylamide (MBA) and 380 mg ammonium persulfate (APS) were weighed and fully dissolved in solution A to form a precursor solution. The precursor solution was incubated at 50 °C for 1 h to obtain PAM-0.5TA hydrogel.
[0049] Example 3
[0050] 4.5 g acrylamide (AAm) and 0.15 g tannic acid (TA) were weighed and dissolved in 15 mL deionized water to form solution A. Subsequently, 10 mg N, N'-methylenebisacrylamide (MBA) and 640 mg ammonium persulfate (APS) were weighed and fully dissolved in solution A to form a precursor solution. The precursor solution was incubated at 50 °C for 1 h to obtain PAM-1TA hydrogel.
[0051] Example 4
[0052] 4.5 g acrylamide (AAm) and 0.3 g tannic acid (TA) were weighed and dissolved in 15 mL deionized water to form solution A. Subsequently, 10 mg N, N'-methylenebisacrylamide (MBA) and 900 mg ammonium persulfate (APS) were weighed and fully dissolved in solution A to form a precursor solution. The precursor solution was incubated at 50 °C for 1 h to obtain PAM-2TA hydrogel.
[0053] The tensile properties of the hydrogels prepared with different amounts of tannic acid added in Examples 1 to 4 were studied.
[0054] The hydrogel in the mold was taken out, and the unreacted monomers on the surface were removed with deionized water, and then the surface moisture was absorbed with filter paper. The two ends of the hydrogel were clamped on the tensile testing machine to ensure that the hydrogel hung naturally. The tensile test was carried out at a tensile speed of 100 mm / min to test its tensile properties. The results are shown in Figure 1 As shown. Figure 1 It can be concluded that with the increase of tannic acid addition, the tensile properties of the hydrogel gradually decreased.
[0055] The adhesion properties of the hydrogels with different tannic acid addition amounts in Examples 1 to 4 were studied by shear overlap tensile method.
[0056] First, a hydrogel patch (20mm×20mm×2mm) was used to adhere one end of the test material, and then another piece of test material was used to adhere it. The tensile test was performed using a tensile testing machine with a tensile rate of 30mm / min. The maximum tensile force during the stretching process was recorded and calculated using the formula: σ=FMAX / S, where σ is the hydrogel stress, Pa; FMAX is the maximum tensile force, N; S is the force-bearing area, m 2 .
[0057] The results are as follows Figure 2 As shown, Figure 2 The adhesion performance of the hydrogel on different test materials, glass, plastic and pig skin, is shown. Figure 2 It can be concluded that the PAM-1AT hydrogel prepared in Example 3 has better adhesion properties. Combining the results of tensile properties and adhesion properties, the method of Example 3 is preferably used to prepare the drug release layer hydrogel.
[0058] Example 5
[0059] Weigh 0.2g of sodium alginate (Alg) and dissolve it in 9.8g of deionized water to obtain a 2wt% sodium alginate solution, then weigh 0.02g of curcumin (Cur) and evenly disperse it in the sodium alginate solution to obtain a sodium alginate-curcumin mixed solution. Weigh 2.2197g of anhydrous calcium chloride (CaCl2) and dissolve it in deionized water, and finally dilute it to 10 mL to obtain a 2M calcium chloride solution. Weigh 1.6g of sodium hydroxide (NaOH) and dissolve it in deionized water, and finally dilute it to 20 mL to obtain a 2M sodium hydroxide solution. Take 1.2mL of 2M calcium chloride solution and 4.8mL of 0.5M ethylenediaminetetraacetic acid (EDTA) solution and mix them evenly, add 2M sodium hydroxide solution to adjust the pH to 7.2~7.4, and finally dilute it to 10mL to obtain a mixed solution. The mixed solution and the sodium alginate-curcumin mixed solution are evenly mixed in equal volumes, and filtered with a 1mL syringe with a needle to obtain an aqueous phase liquid. 5 mL of span-80 was measured and mixed evenly with 95 mL of liquid paraffin to obtain an oil phase liquid. 0.5 mL of glacial acetic acid was measured and mixed evenly with 49.5 mL of the oil phase liquid to obtain a solidified liquid. Figure 3 As shown, the microfluidic device includes a first syringe pump 1 and a second syringe pump 2, the first syringe pump 1 is detachably connected to a first syringe 11, the second syringe pump 2 is detachably connected to a second syringe 12, the second syringe 12 is connected to a transparent hose 14, the end of the transparent hose 14 is connected to a capillary glass tube 13, and the needle of the first syringe 11 is injected into the capillary glass tube 13. The end of the capillary glass tube 13 is injected into the solidifying liquid.
[0060] The first syringe 11 absorbs the aqueous phase liquid and is fixed to the first syringe pump 1, and the second syringe 12 absorbs the oil phase liquid and is fixed to the second syringe pump 2. One end of the transparent hose 14 is connected to the second syringe 12, and the other end is connected to the capillary glass tube 13, wherein a small part of the capillary glass tube 13 is wrapped by the transparent hose 14. The first syringe 11 is connected to the corresponding needle, the needle is bent, and then the front end of the needle is inserted into the transparent hose 14 and inserted into the small part of the capillary glass tube 13 wrapped by the transparent hose 14. The flow rate of the first syringe pump 1 is set to 0.02mL / min, and the flow rate of the second syringe pump 2 is set to 0.27mL / min. First, the second syringe pump 2 is operated to exhaust the air in the system, and then the first syringe pump 1 is operated. When small balls with uniform spacing appear in the capillary glass tube 13, a container containing a solidifying liquid is placed under the capillary glass tube 13 so that the end of the capillary glass tube 13 is located below the liquid surface. Sodium alginate microspheres loaded with curcumin will be produced in the container. After curing for 30 minutes, the microspheres are washed with isopropanol and deionized water, and freeze-dried for use.
[0061] Morphology, particle size statistics and composition analysis of Alg@Cur microspheres.
[0062] The prepared microspheres were dispersed in deionized water, the dispersion was dropped on a glass slide, and the morphology of the microspheres was observed under a microscope. Figure 8 As shown in a, Figure 8 a shows that the prepared Alg@Cur microspheres are relatively uniform in morphology. ImageJ was used to analyze the Alg@Cur microspheres and the particle size distribution of the Alg@Cur microspheres was statistically analyzed. Figure 8 As shown in b, Figure 8 b shows that the particle size of Alg@Cur microspheres is mostly 280~340μm. The results of Fourier infrared detection of Alg@Cur microspheres are as follows Figure 8 As shown in c, Figure 8 c shows that curcumin (Cur) was successfully loaded into sodium alginate (Alg) microspheres.
[0063] Example 6
[0064] 4.5 g acrylamide (AAm) and 0.15 g tannic acid (TA) were weighed and dissolved in 15 mL deionized water to form solution A. Then 10 mg N, N'-methylenebisacrylamide (MBA) and 640 mg ammonium persulfate (APS) were weighed and fully dissolved in solution A to form solution B. 0 g, 0.075 g, 0.15 g, and 0.3 g of sodium alginate microspheres loaded with curcumin (Alg@Cur) were added to solution B, respectively, and ultrasonicated for 10 min to form a homogeneous drug release layer hydrogel precursor solution. The drug release layer hydrogel precursor solution was incubated at 50 °C for 1 h to obtain drug release layer hydrogels with different Alg@Cur contents, which were named PT, PT-0.5C, PT-1C, and PT-2C, respectively.
[0065] The cytotoxicity and tensile properties of the drug release layer hydrogels prepared with different Alg@Cur addition amounts in Example 6 were investigated.
[0066] Mouse fibroblast L929 was inoculated on a 96-well plate at a density of 10,000 cells / well and cultured for 24 hours. The cytotoxicity test was tested using the extract method: the prepared drug release layer hydrogels with different Alg@Cur addition amounts were immersed in DMEM complete cell culture medium (containing 10% FBS) for 24 hours. The extract was then used for co-culture with L929 cells, and the cells in the control group were cultured with DMEM complete cell culture medium. The cytotoxicity assay was performed using a CCK-8 kit, as shown in Figure 4 As shown, the cell activity of the extract group was above 80%, which was within the safe range.
[0067] Take out the hydrogel from the mold, remove the unreacted monomers on the surface with deionized water, and then use filter paper to absorb the surface moisture. Clamp the two ends of the hydrogel on the tensile testing machine to ensure that the hydrogel hangs down naturally. Perform a tensile test at a tensile speed of 100 mm / min to test its tensile properties. Figure 4 and Figure 5 The preferred amount of added Alg@Cur microspheres is 0.15 g to prepare the drug release layer hydrogel.
[0068] Example 7
[0069] Preparation of double-layer hydrogel patch PPTC.
[0070] (1) Weigh 4.5 g of acrylamide (AAm) and 0.15 g of tannic acid (TA) and dissolve them in 15 mL of deionized water to obtain a mixed solution A.
[0071] (2) 0.15 g of sodium alginate microspheres loaded with curcumin (Alg@Cur) were uniformly dispersed in mixed solution A to obtain mixed solution B.
[0072] (3) Dissolve 10 mg of cross-linking agent N,N'-methylenebisacrylamide (MBA) and 0.64 g of initiator ammonium persulfate (APS) in mixed solution B to obtain a drug release layer hydrogel precursor solution.
[0073] (4) Pour the drug release layer hydrogel precursor solution into a 10 cm diameter culture dish and incubate at 50 °C for 1 h to obtain a drug release layer hydrogel.
[0074] (5) The basic components of polydimethylsiloxane (PDMS) and the curing agent are uniformly mixed at a ratio of 10:1 to obtain an antifouling layer precursor solution.
[0075] (6) 4 g of the antifouling layer precursor solution was cast onto the drug release layer hydrogel and incubated at 50 °C for 1 h to obtain a double-layer hydrogel patch.
[0076] The in vitro degradation performance of double-layer hydrogel PPTC at different pH values was investigated.
[0077] The double-layer hydrogel PPTC with the same shape and size was prepared by Example 7, and PBS solutions with different pH were prepared. The pre-prepared hydrogel samples were immersed in a certain volume of different PBS solutions and placed in a shaker (37°C, 120 rpm). The hydrogel samples were collected at different time points, and the collected hydrogel samples were freeze-dried and weighed (Wt), and the degradation rate was calculated by (W0-Wt) / W0×100% (W0 is the initial weight of the hydrogel). Figure 6 It was concluded that PPTC hydrogel could maintain long-term stability.
[0078] The swelling properties of double-layer hydrogel PPTC were investigated.
[0079] The bilayer PPTC was immersed in a certain volume of PBS solution and placed in a shaker (37°C, 120 rpm). The hydrogel was collected at a predetermined time point and weighed (Wt) after removing excess fluid with filter paper. The swelling ratio was calculated as follows: swelling ratio = (Wt-W0) / W0 × 100% (W0 is the initial weight of the hydrogel). Figure 6 As shown, Figure 7 It was concluded that PPTC hydrogel had good swelling properties and could absorb wound exudate and keep the wound microenvironment moist.
[0080] To study the healing performance of double-layer hydrogel patch on infected wounds.
[0081] The SD rat back infected wound was used as an animal model to test the effect of the prepared double-layer hydrogel patch that responds to pH and releases drugs on demand on the healing of infected wounds. The specific operation is as follows: first, the experimental rats were anesthetized to establish an infected wound model, and the back hair was removed after anesthesia. After that, a circular wound (8 mm in diameter) was made on both sides of the back. Then 100μL (108 CFU / mL) of Staphylococcus aureus suspension was injected to create an infected wound. Four groups were set up for the experiment, namely the control group (normal wound was not treated with any material), the PP group (the material was a double-layer hydrogel patch without adding tannic acid TA and Alg@Cur microspheres), the PPT group (a double-layer hydrogel patch without adding Alg@Cur microspheres) and the PPTC group (a double-layer hydrogel patch with TA and Alg@Cur microspheres). There were 4 mice in each group. 24 hours after the injection of Staphylococcus aureus suspension, the material was applied to the wound and replaced every 3 days. The results are shown in the figure. Fig. 9 As shown, it can be seen that the wound healing effect of the PPTC group is the best.
[0082] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a double-layer hydrogel patch for on-demand drug release in response to pH, characterized in that: The steps include: Sodium alginate microspheres loaded with curcumin are prepared by using a microfluidic device; the method comprises: preparing an aqueous phase liquid: preparing a sodium alginate / curcumin aqueous solution, a calcium chloride aqueous solution, a sodium hydroxide aqueous solution and an ethylenediaminetetraacetic acid solution respectively; mixing the calcium chloride aqueous solution with the ethylenediaminetetraacetic acid solution and adjusting the pH to 7.2-7.4 with a sodium hydroxide aqueous solution to obtain a mixed component, and mixing the sodium alginate / curcumin aqueous solution with the obtained mixed component in equal proportions to obtain an aqueous phase liquid; preparing an oil phase liquid: taking liquid paraffin containing 5% span-80 as the oil phase liquid; preparing a solidifying liquid: taking a liquid paraffin containing 1% acetic acid and 5% Span-80 liquid paraffin is used as a solidifying liquid; a first syringe is used to absorb the water phase liquid and then fixed on the first syringe pump, and a second syringe is used to absorb the oil phase liquid and then fixed on the second syringe pump, wherein the outlet end of the first syringe and the outlet end of the second syringe are connected to a capillary glass tube; the second syringe pump is first operated to exhaust the air in the system, and then the first syringe pump is operated, and when small balls with uniform spacing appear in the capillary glass tube, a container containing the solidifying liquid is placed under the capillary glass tube so that the end of the capillary glass tube is located below the liquid surface, and sodium alginate microspheres loaded with curcumin are generated in the container, and the microspheres are washed with isopropyl alcohol and deionized water after solidification, and freeze-dried for standby use; Preparation of drug release layer hydrogel: acrylamide and tannic acid are dissolved in deionized water, the prepared sodium alginate microspheres loaded with curcumin are added and uniformly dispersed by ultrasound, a crosslinking agent and an initiator are added after the dispersion is completed, and after they are completely dissolved, they are placed in an oven for incubation to obtain a drug release layer hydrogel; Preparation of a double-layer hydrogel patch: polydimethylsiloxane and a curing agent are uniformly mixed, cast on the prepared drug-releasing layer hydrogel, and then placed in an oven for curing to form a protective layer on the drug-releasing layer to obtain a double-layer hydrogel patch.
2. The preparation method according to claim 1, characterized in that: The flow rate of the aqueous phase liquid in the first syringe pump is 0.02 mL / min, and the flow rate of the oil phase liquid in the second syringe pump is 0.27 mL / min.
3. The preparation method according to claim 2, characterized in that: The curing time is 30 minutes.
4. The preparation method according to claim 1, characterized in that: In the step of preparing the drug release layer hydrogel, the temperature of the oven is 50° C. and the incubation time is 1 h.
5. The preparation method according to claim 1, characterized in that: In the step of preparing the drug-releasing layer hydrogel, the cross-linking agent is N,N'-methylenebisacrylamide, and the initiator is ammonium persulfate.
6. The preparation method according to claim 1, characterized in that: In the step of preparing the double-layer hydrogel patch, the temperature of the oven is 50° C., the curing time is 1 hour, and the mass ratio of the polydimethylsiloxane to the curing agent is 10:
1.
7. A double-layer hydrogel patch that releases drugs on demand in response to pH, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
8. The double-layer hydrogel patch for on-demand drug release in response to pH according to claim 7, characterized in that: It comprises a drug-releasing layer and a protective layer, wherein the protective layer is attached to the surface of the drug-releasing layer.
Citation Information
Patent Citations
Preparation and application of multi-antibacterial intelligent response hydrogel
CN118403210A